OPTIMALISASI PERKEMBANGAN ANAK DI MASA KEEMASAN - Maya Oktaviani,; Uswatun Hasanah; Elmanora; Annisa Dwi Rahmadina; Annisa Zakiyah Tribrilianti; Intan Wulandari (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Negeri Jakarta, 2022)
Abstract The golden age is a very effective and essential period for optimizing the various intelligence potentials possessed by children to achieve quality human resources. Many families need to learn about the indicators children must achieve at each stage of development and every aspect of their development. This issue impacts parents' inability to provide appropriate care to optimize child development, especially during the golden age. Families need assistance from cadres in optimizing children's development, especially during the golden age. Unfortunately, only some Family Welfare Empowerment (FWE) cadres know how to measure and assess children's developmental achievements. At the same time, the measurement and assessment results of child development are the basis for determining the right parenting style. So there needs to be training for FWE cadres regarding the measurement and development of children so that families or parents can provide the right parenting style and support optimal child development. The solution to overcome this problem is to optimize the development of children in the golden age through the Training of Trainers measuring and assessing child development in Pantai Mekar Village, Muara Gembong District, Bekasi Regency, West Java Province. The participants were enthusiastic about paying attention to the material presentation session. Participants are also able to conduct interactive discussions. In the question and answer session, some participants presented a real case in the Pantai Mekar Village regarding children's growth and development that was not optimal. The participants were satisfied with this activity. Unfortunately, during the activity implementation, no children under five came to the Mekar Beach Village Office hall, so participants could not directly measure children's growth. Abstrak Masa keemasan merupakan masa yang sangat efektif dan esensial untuk mengoptimalkan berbagai potensi kecerdasan yang dimiliki anak untuk mencapai sumber daya manusia yang berkualitas. Banyak keluarga perlu belajar tentang indikator-indikator yang harus dicapai anak-anak pada setiap tahap perkembangan dan setiap aspek perkembangan mereka. Hal ini berdampak pada ketidakmampuan orang tua dalam memberikan pengasuhan yang tepat untuk mengoptimalkan tumbuh kembang anak, terutama pada masa keemasan. Keluarga membutuhkan pendampingan kader dalam mengoptimalkan tumbuh kembang anak, terutama pada masa keemasan. Sayangnya, hanya sebagian kader Pemberdayaan Kesejahteraan Keluarga (PKK) yang mengetahui cara mengukur dan menilai capaian tumbuh kembang anak. Sementara itu, hasil pengukuran dan penilaian tumbuh kembang anak menjadi dasar dalam menentukan pola asuh yang tepat. Sehingga perlu adanya pelatihan bagi kader PKK mengenai pengukuran dan perkembangan anak agar keluarga atau orang tua dapat memberikan pola asuh yang tepat dan mendukung tumbuh kembang anak yang optimal. Solusi untuk mengatasi permasalahan tersebut adalah dengan mengoptimalkan tumbuh kembang anak di masa keemasan melalui Training of Trainer pengukuran dan penilaian tumbuh kembang anak di Desa Pantai Mekar, Kecamatan Muara Gembong, Kabupaten Bekasi, Provinsi Jawa Barat. Para peserta sangat antusias memperhatikan sesi pemaparan materi. Peserta juga mampu melakukan diskusi interaktif. Dalam sesi tanya jawab, beberapa peserta memaparkan kasus nyata di Desa Pantai Mekar terkait tumbuh kembang anak yang belum optimal. Para peserta merasa puas dengan kegiatan ini. Sayangnya, pada saat pelaksanaan kegiatan, tidak ada balita yang datang ke aula Kantor Desa Pantai Mekar, sehingga peserta tidak bisa mengukur pertumbuhan anak secara langsung.